Dynamic Attention Head Selection Improves Multi-Turn Dialogue Coherence in 7B Parameter Models - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: What is the impact of dynamic attention head selection on multi-turn dialogue coherence scores compared to static multi-head attention in 7B parameter models. 12 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.8/10. This report is a machine-generated literature synthe
Machine-generated literature synthesis.